A Mediated Moderation Model of Recruiting Socially and Environmentally Responsible Job Applicants. Issue 4 (14th May 2013) - Gully, Stanley M.; Phillips, Jean M.; Castellano, William G.; Han, Kyongji; Kim, Andrea
Abstract : Socially and environmentally responsible organizations must attend to the fit of employees with the values of the organization. Recruiting practices are a key tool for ensuring fit with an organization's culture and values. We develop and test a model of the process through which recruitment information about an organization's social and environmental responsibility values differentially affect job seeker perceived fit, attraction, and job pursuit intentions depending on job seekers' desire to have a significant impact through work. Our model of mediated moderation is tested with a sample of 339 actual job seekers using conditional process modeling and nonlinear bootstrapping techniques. Results support expectations that advertisement messages about an organization's social and environmental responsibility values interact with applicants' desire to have a significant impact through work to influence job pursuit intentions through the hypothesized mediational process. Implications of the model for research on recruitment and organizational social and environmental responsibility are discussed.